Electrospun Chitosan-Gelatin Biopolymer Composite Nanofibers for Horseradish Peroxidase Immobilization in a Hydrogen Peroxide Biosensor - Siriwan Teepoo; Phanphruk Dawan; Naris Barnthip (Biosensors, 2017)
A biosensor based on chitosan-gelatin composite biopolymers nanofibers is found to be effective for the immobilization of horseradish peroxidase to detect hydrogen peroxide. The biopolymer nanofibers were fabricated by an electrospining technique. Upon optimization of synthesis parameters, biopolymers nanofibers, an average of 80 nm in diameter, were obtained and were then modified on the working electrode surface. The effects of the concentration of enzyme, pH, and concentration of the buffer and the working potential on the current response of the nanofibers-modified electrode toward hydrogen peroxide were optimized to obtain the maximal current response. The results found that horseradish peroxidase immobilization on chitosan-gelatin composite biopolymer nanofibers had advantages of fast response, excellent reproducibility, high stability, and showed a linear response to hydrogen peroxide in the concentration range from 0.1 to 1.7 mM with a detection limit of 0.05 mM and exhibited high sensitivity of 44 µA∙mM−1∙cm−2. The developed system was evaluated for analysis of disinfectant samples and showed good agreement between the results obtained by the titration method without significant differences at the 0.05 significance level. The proposed strategy based on chitosan-gelatin composite biopolymer nanofibers for the immobilization of enzymes can be extended for the development of other enzyme-based biosensors.